Association between adolescent oral contraceptive use and future major depressive disorder: a prospective cohort study. (12th July 2021) - Anderl, Christine; de Wit, Anouk E.; Giltay, Erik J.; Oldehinkel, Albertine J.; Chen, Frances S.
Abstract : Background: Because of the widespread use of oral contraceptives (OCs) and the devastating effects of depression both on an individual and a societal level, it is crucial to understand the nature of the previously reported relationship between OC use and depression risk. Insight into the impact of analytical choices on the association is important when interpreting available evidence. Hence, we examined the association between adolescent OC use and subsequent depression risk in early adulthood analyzing all theoretically justifiable models. Methods: Data from the prospective cohort study TRacking Adolescents' Individual Lives Survey, among women aged 13–25 years were used. Adolescent OC use (ages 16–19 years) was used as a predictor and major depressive disorder (MDD) in early adulthood (ages 20–25 years), as assessed by the Diagnostic and Statistical Manual of Mental Disorders‐IV oriented Lifetime Depression Assessment Self‐Report and the Composite International Diagnostic Interview, was used as an outcome. A total of 818 analytical models were analyzed using Specification Curve Analysis in 534 adolescent OC users and 191 nonusers. Results: Overall, there was an association of adolescent OC use and an episode of MDD in early adulthood [median odds ratio (OR)median = 1.41; ORmin = 1.08; ORmax = 2.18, p < .001], which was driven by the group of young women with no history of MDD (ORmedian = 1.72; ORmin = 1.21; ORmax = 2.18, p < .001). Conclusions: In summary, adolescent OC use was associated with a small but robust increased risk for experiencing an episode of MDD, especially among women with no history of MDD in adolescence. Understanding the potential side effects of OCs will help women and their doctors to make informed choices when deciding among possible methods of birth control.